2016
DOI: 10.1177/0269215516642605
|View full text |Cite
|
Sign up to set email alerts
|

Effects of action observation treatment in recovery after total knee replacement: a prospective clinical trial

Abstract: adding action observation training to conventional inpatient physiotherapy is associated with a greater degree of recovery in patients who have undergone a primary total knee replacement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
84
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(87 citation statements)
references
References 28 publications
(36 reference statements)
0
84
0
3
Order By: Relevance
“…The quality of all the studies was evaluated with the Cochrane assessment tool. 90% of all studies had a low risk of selective reporting bias (Christakou & Zervas, ; Cupal & Brewer, ; Hoyek, Di Rienzo, Collet, Hoyek, & Guillot, ; Lebon, Guillot, & Collet, ; Mahmoud, ; Moseley, ; Nobusako, Matsuo, & Morioka, ; Park, Song, & Kim, ; Villafañe et al, , ) and only one study had high risk of selection bias (Villafañe et al, ). The domain with the highest percentage of studies (70%) with high risk of bias was the blinding of participants and personnel (performance bias; Christakou & Zervas, ; Cupal & Brewer, ; Hoyek et al, ; Moseley, ; Nobusako et al, ; Park et al, ; Villafañe et al, ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The quality of all the studies was evaluated with the Cochrane assessment tool. 90% of all studies had a low risk of selective reporting bias (Christakou & Zervas, ; Cupal & Brewer, ; Hoyek, Di Rienzo, Collet, Hoyek, & Guillot, ; Lebon, Guillot, & Collet, ; Mahmoud, ; Moseley, ; Nobusako, Matsuo, & Morioka, ; Park, Song, & Kim, ; Villafañe et al, , ) and only one study had high risk of selection bias (Villafañe et al, ). The domain with the highest percentage of studies (70%) with high risk of bias was the blinding of participants and personnel (performance bias; Christakou & Zervas, ; Cupal & Brewer, ; Hoyek et al, ; Moseley, ; Nobusako et al, ; Park et al, ; Villafañe et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…The total number of participants was 227. Knee surgery was the complaint of participants in six studies (Cupal & Brewer, ; Lebon et al, ; Mahmoud, ; Moukarzel et al, ; Park et al, ; Villafañe et al, ) and one was hip surgery (Villafañe et al, ). In three studies the participants were diagnosed with chronic pain (Hoyek et al, ; Moseley, ; Nobusako et al, ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, a large amount of evidence has demonstrated that AOT can enhance the beneficial effects of physiotherapy by reinforcing high-level brain networks involved in motor planning and execution, by promoting imitation learning and motor control relearning [ 13 , 18 ] in the elderly [ 19 ] and in patients with orthopaedic [ 20 ] and neurological diseases [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…After this, the PT applied passive end-range motion and stretched the knee connective tissues without causing pain. Then, the patients were submitted to strengthening exercises addressed to the knee extensors, hip lateral rotators and abductors (Rabelo et al, 2014; Villafañe et al, 2017).…”
Section: Methodsmentioning
confidence: 99%